New Representative of the Family Hydroscaphidae from Tunguska Basin, the Boundary of the Permian and Triassic (Coleoptera, Myxophaga) with Review on Myxophagan Fossil R ecords (Global Journal of Science Frontier Research, 2023)
Palaeoscapha tunguskaensis gen. et sp. nov., the oldest representative of the family Hydroscaphidae, is described from the Tunguska Basin in Siberia, dated from the boundary of the Permian and Triassic. It is assigned to the subfamily Triamyxinae, stat. nov. New diagnoses of the Hydroscaphidae and Triamyxinae are proposed. The new subfamily Leehermaniinae subfam. nov. (type genus Leehermania) is erected. The fossil record of the suborder Myxophaga is reviewed and revised with some taxonomic notes and synonymy of some generic and species names in the family Lepiceridae, known from Burmese amber. Different aspects of the evolutionary history of this suborder are discussed. A synonymy of Haplochelus and Lepiceratus is proposed.
Keywords: Lepiceridae; Spheriusidae; Torridincolidae; Triamixinae; Leehermaniinae; evolutionary history; new subfamily